Prevalence of antenatal depression and its association with adverse childhood experiences: a cross- sectional study at Hospital Canselor Tuanku Muhriz, Kuala Lumpur - Nagenthiran, Lalijah; Abd Rahman, Fairuz Nazri; Mahadevan, Raynuha; Zainuddin, Ani Amelia; Sutan, Rosnah (Frontiers in Psychiatry, 2025)
IntroductionEmerging evidence suggests a link between adverse childhood experiences (ACEs) and antenatal depression, with a higher number of maternal ACEs associated with increased depressive symptoms during pregnancy.ObjectiveThis study aimed to assess the prevalence of antenatal depression and its association with ACEs among pregnant women in a hospital setting. Methods: A cross-sectional study was conducted among 314 pregnant women recruited through convenience sampling between 18th November 2024 to 31st December 2024. Inclusion criteria were pregnant women aged 18 years and older, able to communicate in English or Malay, able to consent, and Malaysian citizens. Data collection involved self- reported sociodemographic questionnaire, the Edinburgh Postnatal Depression Scale (EPDS) and Adverse Childhood Experiences– International Questionnaire (ACE -IQ). Participants were stratified by ACE score groupings (0, 1, 2, 3, ≥4), and associations with depression risk were analyzed using logistic regression models, adjusting for confounders such as race, occupation, planned pregnancy, and trimester. The association between specific ACE domains and depression risk was also explored.ResultsThe prevalence for antenatal depression was 13.7%. with 70.4% reporting at least one ACE. Higher ACE scores were significantly associated with increased depression risk. Women with four or more ACEs had more than a sevenfold increased odds of depression (OR = 7.3, 95% CI = 2.79, 18.71, p < 0.001). In adjusted models, the association persisted (aOR = 4.60, 95% CI = 1.32, 16.02, p = 0.017). Specifically, physical abuse (aOR = 5.08, 95% CI = 2.20, 11.73, p < 0.001), emotional abuse (aOR = 3.54, 95% CI = 1.66, 7.58, p = 0.001), household member treated violently (aOR = 4.400, 95% CI = 1.94, 9.96, p < 0.001), physical neglect (aOR = 2.65, 95% CI = 1.26, 5.59, p = 0.010), and community violence (aOR = 2.16, 95% CI = 1.08, 4.33, p = 0.030) were all significantly related to depression risk.ConclusionOur findings suggest that ACEs are strongly associated with an increased risk of depression among pregnant women and highlights the importance of integrating depression and ACE screening into antenatal services.